2009
DOI: 10.1175/2009jtecha1283.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Compact Cryogenic Air Sampler and Its Application in Stratospheric Greenhouse Gas Observation at Syowa Station, Antarctica

Abstract: To collect stratospheric air samples for greenhouse gas measurements, a compact cryogenic air sampler has been developed using a cooling device called the Joule–Thomson (J–T) minicooler. The J–T minicooler can produce liquefied neon within 5 s from high pressure neon gas precooled by liquid nitrogen. The sampler employs liquid neon as a refrigerant to solidify or liquefy sampled atmospheric constituents. Laboratory experiments showed that the sampler is capable of collecting about 3 and more than 7 L STP of ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…1. The cryogenic air sampler is equipped with a cooling device called a JouleThomson (J-T) mini-cooler in which neon is liquefied to be used as a refrigerant for collecting stratospheric air cryogenically (Morimoto et al, 2009). Eight sets of cryogenic air samplers and four large plastic balloons were prepared for the Biak campaign.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. The cryogenic air sampler is equipped with a cooling device called a JouleThomson (J-T) mini-cooler in which neon is liquefied to be used as a refrigerant for collecting stratospheric air cryogenically (Morimoto et al, 2009). Eight sets of cryogenic air samplers and four large plastic balloons were prepared for the Biak campaign.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, air sampling was performed during balloon ascent. In the past, we conducted a number of similar air samplings using a cryogenic sampler with liquid helium (Honda et al, 1996) in which we collected samples during the balloon ascent and descent over Japan; they showed that the outgassing from the balloon and payload had a negligibly small impact on the air sample quality even if air sampling was made during the balloon ascent (Morimoto et al, 2009;. One sampler assigned to 21 km leaked after landing due to a defect in electric circuit.…”
Section: Methodsmentioning
confidence: 99%
“…Air samples were collected from the stratosphere over Syowa using two types of samplers; the first was a cryogenic air sampler with liquid helium as a coolant (Honda et al 1996), hereafter referred to as the cryo-sampler; the other was a compact cryogenic air sampler equipped with a Joule-Thomson mini cooler (Morimoto et al 2009), hereafter referred to as the JT-sampler. Stratospheric air was collected using the cryo-sampler on 3 January 1998, 26 December 2003, and 5 January 2004 (Sugawara et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The JT-sampler was used to collect stratospheric air on 4 January 2008, 31 December 2012, and 10 January 2013. The air sampling procedures using the two samplers are described in detail in Nakazawa et al (1995) and Morimoto et al (2009). By performing the air storage tests over 1−3 months for each sampler, the measured CO 2 mole fraction values of the air collected in the JT-sampler were corrected by 0.0−1.0 ppm, while no correction was applied to those in the cryo-sampler.…”
Section: Methodsmentioning
confidence: 99%
“…2 Experiments and model simulation 2.1 Whole air sampling over the Equator Stratospheric air samples were collected using balloon-borne compact cryogenic samplers (J-T samplers) (Morimoto et al, 2009 (Hasebe et al, 2018). For each balloon flight, two samplers integrated into a single gondola were launched from the observatory of the National Institute of Aeronautics and Space of the Republic of Indonesia (LAPAN).…”
Section: Introductionmentioning
confidence: 99%